Design and thermal performances of Semi-Parabolic Linear Fresnel Reflector solar concentration collector - Zhu, Jie; Huang, Hulin (Elsevier, 2014)
A Semi-Parabolic Linear Fresnel Reflector (SPLFR) solar concentrator is proposed in this paper. The SPLFR is formed by linear plate mirrors whose edges located at a parabolic line. The ray trace simulation results show the SPLFR has the same concentrating efficiency as that of the parabolic trough concentrator (PTC), but lower manufacture cost. The SPLFR concentrator has higher ground utilization ratio compared with that of Linear Fresnel Reflector (LFR) concentrator because it has no shading and blocking shortcomings. The SPLFR concentrated radiation distribution along the circumference of absorber pipe cross section is investigated and compared with that of LFR concentrator. The thermal performance of linear evacuated absorber for the SPLFR is simulated numerically as well. The nonuniform radiation distribution induces two convection eddies at each side of absorber pipe which enhances the heat transfer from the wall of absorber to the working fluid.